KONSEPTUALISASI MASYARAKAT MANGGARAI TENTANG BUDAYA LONTO LEOK SEBAGAI PIRANTI HUKUM ADAT RESPONSIF-SOSIOLOGIK DALAM RANGKA PENYELESAIAN KONFLIK PERTANAHAN DAN PEMERTAHANAN HARMONI SOSIAL - Fransiskus Bustan Agustinus Mahur (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2019)
This study explores the conceptualisation of Manggarai people on lonto leok culture (LLC) as a responsive-sociologic customary law device in solving land conflict and maintaining social harmony in view of cultural linguistics. In terms of its focus, the study is a decriptive study. The procedures of research were field and library research. The data wera analyzed qualitatively by using inductive method as the analysis was started from the data to the theory or concept dealing with the conceptualisation of Manggarai people on the conceptualisation of Manggarai people on the LLC as a responsive-sociologic customary law device in solving land conflict and maintaining social harmony in view of cultural linguistics. The results of research show that there are several verbal expressions in Manggarai language in which their forms and meanings reflect the function of LLC as a responsive-sociologic customary law device in an attempt to solve land conflicts and maintain social harmony for Manggarai people. The verbal expressions are as follows: (1) Muku ca pu’u neka woléng curup, téu ca ambo néka woléng lako, (2) Ipung ca tiwu neka woleng wintuk, nakeng ca wae neka woleng tae, (3) Ase-kae ca sosor wae neka woleng tae, ase -ka’e ca natas labar neka woleng bantang, and (4) Padir wa’i, rentu sa’i, bantang cama, reje leles nai ca anggit, tuka ca léléng.The result of this study might be beneficial as a source of reference in designing the model of revitalizing the LLC.